Facial reactions to emotional films in young children with conduct problems and varying levels of callous‐unemotional traits. (20th September 2022) - Kimonis, Eva R.; Le, Brandon; Fleming, Georgette E.; Kyranides, Melina N.; Demetriou, Chara A.; Fanti, Kostas A.; Neo, Bryan; Prasad, Ashneeta H.; Chan, Amanda; Hawes, David J.; Eapen, Valsamma
Abstract : Background: Elevated levels of callous‐unemotional (CU) traits have proven useful for identifying a distinct subgroup of children whose conduct problems (CP) are early emerging, severe, persistent, and underpinned by aberrant emotional processing. The early childhood emotional experiences and expressions of CP subtypes are poorly understood, despite their importance to understanding the problematic attachments and atypical social affiliation experienced by children with elevated CU traits. The current study aimed to test for differences in facial emotional reactions to mood‐inducing film clips in children with CP and varying levels of CU traits. Method: We compared facial emotional reactions during a developmentally appropriate mood induction task in a mixed‐sex sample of clinic‐referred preschool children ( M age  = 3.64 years, SD  = 0.63, 66.9% male) classified as CP with elevated levels of CU traits (CP + CU; n  = 25) versus low CU traits (CP‐only; n  = 47), and typically developing children (TD; n  = 28). Results: Relative to TD children, children with clinical CP showed less congruent and more incongruent facial emotional expressions to sad and happy film clips, controlling for child sex, age, and ethnicity. Conclusions: Consistent with older samples, young children with CP show atypical facial emotional expressions in response to positive and negative emotional stimuli. Findings have implications for developmental models of childhood antisocial behavior and can inform the development of targeted interventions.